Gastrointestinal Hormones Manipulation to Counteract Metabolic Syndrome Using Duodenal Targeted Embolization. (June 2019) - Pop, Raoul; Kong, Seong-Ho; Langlois, Allan; Marchegiani, Francesco; Shlomovitz, Eran; Legnèr, András; Bietiger, William; Pinget, Michel; Beaujeux, Rémy; Mutter, Didier; Marescaux, Jacques; Diana, Michele
Purpose . Targeted embolization of gastrointestinal (GI) arteries can modify hormonal production. We aimed to evaluate the impact of the embolization of the gastroduodenal artery (GDA) on the activity of foregut mucosa. Methods . The GDA's duodenal branch was embolized in 12 Yucatan pigs using 100-300 µm (group A; n = 4) or 300-500 µm (group B; n = 4) microspheres, followed by coiling of the branch. In 4 animals (sham), only saline was injected. The levels of GI hormones (ghrelin, glucose-dependent insulinotropic peptide [GIP], glucagon-like peptide-1 [GLP-1], insulin, peptide YY [PYY], leptin) and the gene expression of sodium-glucose–linked transporter-1 (SGLT-1) and glucose transporter-2 (GLUT-2) were assessed before (T0), 1 hour (T1), 1 month (T2), 3 months (T3), and 6 months (T4) after embolization. Results . In group A, a segmental duodenal stenosis occurred in all cases, which required balloon dilatation. There was a significant drop in the baseline glycemia in group A at T1 and T4 versus sham. Ghrelin was reduced in group A versus baseline and versus group B at T2 and T3 and versus sham at T1 and T3. Insulin was significantly lower in group A versus B at T1 and at T4 but not versus sham. SGLT-1 expression increased in B and sham at T4, while it remained stable in group A. GLUT-2 expression increased in sham at T4 but not in A or B. Conclusions . GDA embolization induced a decrease in ghrelin production and influenced expression of glucose carriers in the foregut mucosa.